Efek Iyengar Yoga terhadap Keseimbangan Dinamis pada Populasi Lanjut Usia: Tinjauan Pustaka - Jasmine Putri Nabila; Helmi Ismunandar; Arif Yudho Prabowo; Ahmad Fauzi (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
The rapid aging of Indonesia’s population has significantly increased fall risk among older adults, underscoring the need for safe, effective non-pharmacological interventions to improve dynamic balance. This systematic literature review aimed to evaluate current evidence (2020–2025) on the effects of Iyengar yoga on dynamic balance in older adults. Following PRISMA 2020 guidelines, a Scopus search identified four studies meeting inclusion criteria from an initial 46 records; these were subsequently analyzed using the PICOS framework. Results consistently demonstrated that Iyengar yoga significantly enhanced postural stability, muscle strength, flexibility, proprioception, balance confidence, and cognitive functions (attention and working memory), while indirect benefits through stress reduction further strengthened motor coordination. The intervention proved highly safe, exhibited excellent adherence, and was successfully delivered online. However, its direct impact on fall prevention remained variable. Iyengar yoga is therefore confirmed as an effective holistic intervention for improving multiple components of dynamic balance in older adults. It is recommended that programs be enriched with multidirectional reactive exercises and fall-prevention education to optimize real world fall reduction outcomes. Keywords: Iyengar Yoga; Dynamic Balance; Seniors; Eldely People